Enhanced emergence of antibiotic-resistant pathogenic bacteria after in vitro induction with cancer chemotherapy drugs. (20th February 2019) - Meunier, Alexandre; Nerich, Virginie; Fagnoni-Legat, Christine; Richard, Marion; Mazel, Didier; Adotevi, Olivier; Bertrand, Xavier; Hocquet, Didier
Abstract: Background: Infections with antibiotic-resistant pathogens in cancer patients are a leading cause of mortality. Cancer patients are treated with compounds that can damage bacterial DNA, potentially triggering the SOS response, which in turn enhances the bacterial mutation rate. Antibiotic resistance readily occurs after mutation of bacterial core genes. Thus, we tested whether cancer chemotherapy drugs enhance the emergence of resistant mutants in commensal bacteria. Methods: Induction of the SOS response was tested after the incubation of Escherichia coli biosensors with 39 chemotherapeutic drugs at therapeutic concentrations. The mutation frequency was assessed after induction with the SOS-inducing chemotherapeutic drugs. We then tested the ability of the three most highly inducing drugs to drive the emergence of resistant mutants of major bacterial pathogens to first-line antibiotics. Results: Ten chemotherapeutic drugs activated the SOS response. Among them, eight accelerated the evolution of the major commensal E. coli, mostly through activation of the SOS response, with dacarbazine, azacitidine and streptozotocin enhancing the mutation rate 21.3-fold ( P < 0.001), 101.7-fold ( P = 0.01) and 1158.7-fold ( P = 0.02), respectively. These three compounds also spurred the emergence of imipenem-resistant Pseudomonas aeruginosa (up to 6.21-fold; P = 0.05), ciprofloxacin-resistant Staphylococcus aureus (up to 57.72-fold; P = 0.016) and cefotaxime-resistant Enterobacteria cloacae (up to 4.57-fold; P = 0.018). Conclusions: Our results suggest that chemotherapy could accelerate evolution of the microbiota and drive the emergence of antibiotic-resistant mutants from bacterial commensals in patients. This reveals an additional level of complexity of the interactions between cancer, chemotherapy and the gut microbiota.